2021
DOI: 10.3390/ijerph18147715
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Signals on Donation Crowdfunding Campaign Success during COVID-19 Crisis

Abstract: In 2020, the coronavirus pandemic devasted public health agencies and the federal government across the world. Bridging the gap between underserved populations and the healthcare system, the donation-based crowdfunding campaign has opened a new way for suffering individuals and families to access broader social network platforms for financial and non-financial assistance. Despite the growing popularity of crowdfunding during the pandemic crisis, little research has explored the various signals that attract pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…The volume of donations they receive comes primarily from individuals, while corporate houses dominate the donations’ worth. Recent studies have highlighted the importance of individual donors in supporting people’s financial and economic well-being (Behl et al, 2021a , 2021b , 2021c ; Ho et al, 2021 ; Xiao & Yue, 2021 ). While earlier studies have discussed this in DM, recent studies have also highlighted its importance in relation to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of donations they receive comes primarily from individuals, while corporate houses dominate the donations’ worth. Recent studies have highlighted the importance of individual donors in supporting people’s financial and economic well-being (Behl et al, 2021a , 2021b , 2021c ; Ho et al, 2021 ; Xiao & Yue, 2021 ). While earlier studies have discussed this in DM, recent studies have also highlighted its importance in relation to COVID-19.…”
Section: Introductionmentioning
confidence: 99%
“…It can be said that the reach of DDW's social media is not as wide as in previous studies that have been successful in their campaigns and marketing. Han-Chiang Ho et al, (2021) revealed that comments, followers, and shares on social media influence the success of crowdfunding campaigns. This is in line with Abishek Bhati and Diarmuid McDonnell (2020), which revealed that the number of likes on Facebook is positively related to fundraising success.…”
Section: Resultsmentioning
confidence: 99%
“…We would expect similar effects of a quick response in COVID-19 crowdfunding campaigns, and control for the possible impact of Starting month accordingly. Second, given that Hubei was the epicenter of the outbreak, we employ Supported area to control for the geographical effect (Mollick, 2014 ; Ho et al, 2021 ). Finally, following prior research (Liu et al, 2021 ; Mollick, 2014 ), we control for the Fundraising goal .…”
Section: Methodsmentioning
confidence: 99%
“…However, to date very little research has attempted to apply signaling theory to pure donation-based charitable crowdfunding. Ho et al ( 2021 ) discussed how signals originating from campaign- and fundraiser-level attributes as well as from donor–fundraiser interactions influenced the success of food-aid crowdfunding campaigns on GoFundMe during the COVID-19 pandemic. Attempts were also made to examine the success factors of charitable crowdfunding with a reward-based feature (Bukhari et al, 2019 ) and medical crowdfunding (Chen et al, 2022 ) from a signaling theory perspective.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation